(untitled) (World Science, 2021)
The article is devoted to the problem of selection and distribution of known orders for long-distance transportation of goods by small transport companies. The ordering of the incoming flow of orders for transportation of cargoes taking into account time restrictions on their performance is considered. The incoming order flows of such enterprises are stochastic and different in the structure of transport cycles. The random nature of orders leads to the fact that their execution requires additional unproductive costs of the carrier’s resources. It is taken into account that orders for transportation are unequally correlated. The article assumes that the compatibility of two orders, which are performed in a common route by one vehicle, characterizes the additional time spent on mileage and downtime. The pairwise coefficient of order compatibility is the ratio of the "net" time for order fulfillment to the time required for preparatory additional operations and trips in connection with the previous execution of another order. The set of orders can also be characterized by the average group value of the compatibility factor. The theoretical research model is based on the principle that from any set of known and ready to execute orders, you can choose a subset for which the average group compatibility factor is maximum. This means that the selected subset can be performed with greater efficiency by a given fleet of vehicles without the involvement of funds for cooperation. Therefore, the task of operational planning of the park in terms of stochastic input flow can be simplified to linear integer programming. A new version of the problem has been formulated, which allows to find a guaranteed exact solution for a suitable operating time of calculation. The approbation of the theoretical model at search of optimum plans of transportation of cargoes at the small motor transport enterprise is executed. The influence of the average group compatibility coefficient on the total profit of the enterprise from transportations in the form of the regression equation is established. The theoretical model agrees well with the empirical data according to Fisher’s criterion. An algorithm for using the initial analysis of the incoming flow of orders to increase the profitability of the transport company is proposed.